Użytkowanie lasu na potrzeby poligonu wojskowego - Furmanek, Bartosz (Kwartalnik Prawa Publicznego, 2017)
The provisions of the Act of 28 September 1991 on forests enable giving the organizational unit of the State Treasury (Ministry of National Defence) – by the means of contract through giving into usufruct – forest land for the needs of a military training ground. These provisions raise serious interpretation doubts as to the legal form of the access to the property and the unilateral deprivation of the possibility of its use by the unit. In this publication, the author of this article will try to clarify these issues.